Flexible ZIFs: probing guest‐induced flexibility with CO2, N2 and Ar adsorption. Issue 12 (4th March 2019) - Noguera‐Díaz, Antonio; Villarroel‐Rocha, Jhonny; Ting, Valeska P; Bimbo, Nuno; Sapag, Karim; Mays, Timothy J
Abstract: BACKGROUND: The effect of framework topology on the guest‐induced flexibility of several crystalline zeolitic imidazolate frameworks (ZIF‐7, ZIF‐9, ZIF‐11 and ZIF‐12) was investigated via analysis of experimental nitrogen (N2 ), carbon dioxide (CO2 ) and argon (Ar) isotherms at 77 K (N2 and Ar) and 273 K (CO2 ) for gas pressures up to 0.13 MPa. RESULTS: The experimental isotherms of these frameworks were analysed in order to investigate their structural flexibility using gases with kinetic diameters equal to or larger than the diameters of their static pore apertures. The results of gas sorption measurements indicate guest‐induced phase changes for ZIF‐7 and ZIF‐9 (SOD topologies). ZIF‐12 (RHO topology) also shows uptake for gases, despite its pore‐limiting diameter being smaller than the kinetic diameters of the adsorbed molecules. CONCLUSIONS: This work highlights the ability of ZIFs with different framework topologies to change their structure and increase their pore aperture upon interaction with certain gases. These findings are key in the development of more selective ZIF‐based materials for important industrial applications including low‐energy gas separations, catalytic nanoreactors and sensor technology. © 2019 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.